Correction: Optimising Instrumented Mouthguard Data Analysis: Video Synchronisation Using a Cross-correlation Approach - James Tooby; Steve Rowson; Kevin Till; David Allan; Melanie Dawn Bussey; Dario Cazzola; Éanna Falvey; Kenzie Friesen; Andrew J. Gardner; Cameron Owen; Gregory Roe; Thomas Sawczuk; et al. (Annals of Biomedical Engineering, 2025)

Optimising Instrumented Mouthguard Data Analysis: Video Synchronisation Using a Cross-correlation Approach - James Tooby; Steve Rowson; Kevin Till; David Allan; Melanie Dawn Bussey; Dario Cazzola; Éanna Falvey; Kenzie Friesen; Andrew J. Gardner; Cameron Owen; Gregory Roe; Thomas Sawczuk; et al. (Annals of Biomedical Engineering, 2025)
Purpose Head acceleration events (HAEs) are a growing concern in contact sports, prompting two rugby governing bodies to mandate instrumented mouthguards (iMGs). This has resulted in an influx of data imposing financial and time constraints. This study presents two computational methods that leverage a dataset of video-coded match events: cross-correlation synchronisation aligns iMG data to a video recording, by providing playback timestamps for each HAE, enabling analysts to locate them in video footage; and post-synchronisation event matching identifies the coded match event (e.g. tackles and ball carries) from a video analysis dataset for each HAE, this process is important for calculating the probability of match events resulting in HAEs. Given the professional context of iMGs in rugby, utilising commercial sources of coded match event datasets may expedite iMG analysis. Methods Accuracy and validity of the methods were assessed via video verification during 60 rugby matches. The accuracy of cross-correlation synchronisation was determined by calculating synchronisation error, whilst the validity of post-synchronisation event matching was evaluated using diagnostic accuracy measures (e.g. positive predictive value [PPV] and sensitivity). Results Cross-correlation synchronisation yielded mean synchronisation errors of 0.61–0.71 s, with all matches synchronised within 3 s’ error. Post-synchronisation event matching achieved PPVs of 0.90–0.95 and sensitivity of 0.99–1.00 for identifying correct match events for SAEs. Conclusion Both methods achieved high accuracy and validity with the data sources used in this study. Implementation depends on the availability of a dataset of video-coded match events; however, integrating commercially available video-coded datasets offers the potential to expedite iMG analysis, improve feedback timeliness, and augment research analysis.

Method evaluation and risk assessment: A framework for evaluating management strategies for data‐limited fisheries - Thomas R. Carruthers; Quang C. Huynh; Adrian R. Hordyk; David Newman; Anthony D. M. Smith; Keith J. Sainsbury; Kevin Stokes; Alexander Morison; David Agnew; Ana Parma; Ignacio Sobrino; Catherine Longo (Fish and Fisheries, 2023)
Fisheries managers are in need of quantitative tools to inform decisions regarding selection of robust management practices, prioritising research gaps and stocks to focus on, particularly where there are limited resources or data. To support these decisions, the use of Management Strategy Evaluation (MSE), that is, closed loop simulation‐testing of management procedures, is widely regarded as best practice. However, applying MSE is time‐ and computationally intensive, and requires highly skilled expertise and processes for stakeholder input and peer review. For data‐ and capacity‐limited fisheries, MSE may be particularly challenging to implement. Yet, these are the contexts where it is most critical to test assumptions, evaluate the implications of all sources of uncertainty and identify the most informative data sources. To facilitate wider use of MSE, the Method Evaluation and Risk Assessment (MERA) framework was developed as an accessible online interface, with quick processing time, focused on generic data‐limited management procedures, but allowing progression to tailored and more data‐rich methods. The framework links a quantitative questionnaire and data input standard to a flexible operating model with optional customisation via command line access to the back‐end open‐source R libraries. Here, we illustrate a case study application of MERA for the bocinegro ( Pagrus pagrus , Sparidae) fishery in the Gulf of Cadiz, where in conjunction with fishery stakeholders, a custom management procedure was developed and tested and key research gaps and data collection priorities were identified. We discuss implications for wider use of MSE in various contexts, including eco‐certification and fishery improvement projects.

A reduced activity model: a relevant tool for the study of ageing muscle - Oliver Perkin; Polly McGuigan; Dylan Thompson; Keith Stokes (Biogerontology, 2016)

Marine biofilms on artificial surfaces: structure and dynamics - Maria Salta; Julian A. Wharton; Yves Blache; Keith R. Stokes; Jean‐Francois Briand (Environmental Microbiology, 2013)
Summary The search for new antifouling ( AF ) coatings that are environmentally benign has led to renewed interest in the ways that micro‐organisms colonize substrates in the marine environment. This review covers recently published research on the global species composition and dynamics of marine biofilms, consisting mainly of bacteria and diatoms found on man‐made surfaces including AF coatings. Marine biofilms directly interact with larger organisms (macrofoulers) during colonization processes; hence, recent literature on understanding the basis of the biofilm/macrofouling interactions is essential and will also be reviewed here. Overall, differences have been identified in species composition between biofilm and planktonic forms for both diatoms and bacteria at various exposure sites. In most studies, the underlying biofilm was found to induce larval and spore settlement of macrofoulers; however, issues such as reproducibility, differences in exposure sites and biofilm composition (natural multispecies vs. monospecific species) may influence the outcomes.

Different responses of selected hormones to three types of exercise in young men - Keith A. Stokes; Kate L. Gilbert; George M. Hall; Robert C. Andrews; Dylan Thompson (European Journal of Applied Physiology, 2013)

Alterations in flood frequency increase exotic and native species richness of understorey vegetation in a temperate floodplain eucalypt forest - Kate Stokes; Keith Ward; Matthew Colloff (Plant Ecology, 2010)

Effect of 6weeks of sprint training on growth hormone responses to sprinting - Keith A. Stokes; Mary E. Nevill; Paul W. Cherry; Henryk K. A. Lakomy; George M. Hall (European Journal of Applied Physiology, 2004)